Multiplicity-dependent inclusive J/ψ production at forward rapidity in pp collisions at √s=13 TeV - Acharya, S.; Agarwal, A.; Rinella, G. Aglieri; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; Akishina, V.; et al. (SPRINGER, 2025)
This paper presents a study of the inclusive forward J/psi yield as a function of forward charged-particle multiplicity in pp collisions at root s = 13 TeV using data collected by the ALICE experiment at the CERN LHC. The results are presented in terms of relative J/psi yields and relative charged-particle multiplicities with respect to these quantities obtained in inelastic collisions having at least one charged particle in the pseudorapidity range |eta| < 1. The J/psi mesons are reconstructed via their decay into mu(+)mu(-) pairs in the forward rapidity region (2.5 < y < 4). The relative multiplicity is estimated in the forward pseudorapidity range which overlaps with the J/psi rapidity region. The results show a steeper-than-linear increase of the J/psi yields versus the multiplicity. They are compared with previous measurements and theoretical model calculations.
Keywords: Hadron-Hadron Scattering; QCD; Quarkonium; Physics